‘For we shall prejudice nothing’: Middle Way Conservatism and the defence of inequality, 1945–1979 - Blackburn, Dean (SAGE, 2015)
Recent descriptions of British Conservatism have often identified the defence of inequality as one of its core ideological features. By drawing upon Michael Freeden's morphological conception of ideologies, this article will challenge such descriptions. Drawing upon the discourses of a particular formation of post-war Conservative thought, it will suggest that because Conservatives adhered to a particular set of epistemological and ontological beliefs, the defence of inequality could only obtain a subordinate status within their thought. And it will, in turn, critique dominant understandings of post-war party competition.